Performance of type-I Hybrid ARQ using Reed Solomon code / Rozadatul Intan Safrina Che Rus - Che Rus, Rozadatul Intan Safrina (2008)
Reed Solomon code is one of the most effective error control scheme and it is a type of Forward Error Correction (FEC) code. This error control code is normally used in data transmission. Meanwhile, Automatic Repeat Request is another type of error control scheme that is widely used as error detection because of its simplicity. In recent years, there have been numerous researches on the third error control scheme known as Hybrid Automatic Repeat Request or in short Hybrid ARQ. The need to have a reliable transmission and to provide a throughput as high as possible has increased the system complexity and lead to the study of Hybrid ARQ. It is believed that FEC and ARQ can overcome the drawbacks of FEC and ARQ schemes. To realize this, the model of Hybrid ARQ system is modelled. The Reed Solomon code and ARQ protocol are combined to form a hybrid ARQ. The system model of Type-I Hybrid ARQ scheme is developed and its performance is simulated using MATLAB®. This thesis focuses on the performance study of Bit Error Rate (BER) and throughput.